Analisis Program Sahabat Daya Universitas Terhadap Pertumbuhan dan Perkembangan UMKM di Kecamatan Medan Deli - Sri Dinda Nila Sari; Siti Kadariah (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the impact of the Sahabat Daya Universitas Program on the growth and development of MSMEs in Medan Deli District. The study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that MSME actors in Medan Deli District, spread across six villages—Tanjung Mulia Hilir, Tanjung Mulia, Mabar Hilir, Mabar, Titi Papan, and Kota Bangun—face various challenges, such as insignificant income growth, lack of knowledge in offline and online marketing, absence of business identity, and limited funding. Through the Sahabat Daya Universitas Program, in collaboration with the Kampus Merdeka initiative and BTPN Syariah, students and universities act as facilitators to assist MSME actors. The program provides education on marketing and product development, thereby improving market access. Based on interview findings, this program has proven effective in increasing MSME actors' income and expanding product variety. With regular mentoring, the Sahabat Daya Universitas Program can further promote MSME growth in Medan Deli District